The Strategy of Smart Power in Turkish Foreign Policy Toward the Syrian Crisis - Ozcosar, Ibrahim; Sehitoglu, Sadik; Kadad, Mustafa (Journal of Posthumanism, 2024)
The study examines Turkey’s smart power strategy in its foreign policy toward the Syrian crisis during the period (2011–2022). This strategy effectively combined hard power tools (military and economic) with soft power tools (cultural and diplomatic) within a framework aimed at achieving its national and regional interests and adapting to the crisis’s dynamics. The purpose of the study was to analyze Turkish foreign policy and assess its success in achieving its objectives, relying on statements by officials, official publications, documented events, and works by specialists and experts. Turkey’s objectives included safeguarding its national security from the threat of armed Kurdish groups, enhancing its role as an influential regional power, and reshaping the Syrian regime to align with its interests. The study also concluded that Turkey has successfully reduced security threats along its southern borders and has positioned itself as a regional player capable of contributing to the establishment of international peace and security. However, the risk of the emergence of a Kurdish entity in northeastern Syria remains, despite the fall of Bashar al-Assad’s regime.